Insights into Molecular Profiles, Resistance Patterns, and Virulence Traits of Staphylococci from Companion Dogs in Angola - Romay Coragem da Costa; Francisca Guerra Cunha; Raquel Abreu; Gonçalo Pereira; Catarina Geraldes; Eva Cunha; Lélia Chambel; Manuela Oliveira (Animals)
Staphylococci are prevalent in dogs’ microbiota, with commensal strains being able to exhibit resistance and virulence traits, complicating secondary infection management. As antimicrobial resistance is a global threat, particularly in middle-income countries like Angola, surveillance of resistant bacteria is crucial. We analyzed the prevalence, antimicrobial resistance, and virulence profiles of staphylococci from dogs in Angola. Isolates were identified using VITEK® 2 Compact (bioMérieux© SA, Marcy l’Etoile, France), and their genetic diversity was assessed via PCR fingerprinting. Isolates’ susceptibility to relevant antimicrobials was determined by disk diffusion, and their virulence profiles were evaluated using plaque assays. The relationship between antibiotic resistance and animal-related factors was also assessed by statistical analysis. Isolates were identified as Mammaliicoccus sciuri (former Staphylococcus sciuri, 38%), Staphylococcus xylosus (30%), Staphylococcus equorum (13%), Mammaliicoccus vitulinus (former Staphylococcus vitulinus, 7%), Mammaliicoccus lentus (former Staphylococcus lentus, 5%), Staphylococcus aureus (2%), and Staphylococcus spp. (5%). Of these, 86% were resistant to at least one of the antimicrobials tested, and 30% were classified as multidrug-resistant, being more common in females, dogs with clinical signs of disease, and vaccinated animals. Moreover, 93% of the isolates were able to produce biofilm, 46% could produce lecithinase and gelatinase, and 23% could produce hemolysins. Companion dogs from Angola can carry resistant staphylococci able to express several virulence factors, potentially representing a One Health risk.